Single‐Atom Ru Doping Induced Phase Transition of MoS2 and S Vacancy for Hydrogen Evolution Reaction. Issue 12 (11th November 2019) - Zhang, Junmeng; Xu, Xiaopei; Yang, Liu; Cheng, Daojian; Cao, Dapeng
Abstract: Using electrochemical water splitting to produce hydrogen is still a grand challenge due to the lack of economical and efficient Pt‐free catalysts. Herein, a single‐atom Ru supported on MoS2 (SA‐Ru‐MoS2 ) electrocatalyst for the hydrogen evolution reaction (HER) is reported. Results indicate that single‐atom Ru doping induces phase transition of MoS2 and generation of S vacancies, which significantly improve the performance of inert 2D MoS2 for HER. In particular, the SA‐Ru‐MoS2 electrocatalyst exhibits a low overpotential of 76 mV at 10 mA cm −2 in alkaline media, which is superior to most electrocatalysts previously reported in the literature. Combining experimental results with density functional theory (DFT) calculations, it is further revealed that the origin of high HER activity is mainly attributed to the synergy effects of single‐atom Ru doping and S vacancies and phase transition of local structure of MoS2, which efficiently tailors the electronic structure of SA‐Ru‐MoS2 and extremely reduces the energy barrier of the Volmer step and the adsorption/desorption of H* intermediate step. In short, this work provides a single‐atom doping strategy to transfer the inert MoS2 into the highly efficient electrocatalysts. Abstract : A single‐atom ruthenium supported on MoS2 electrocatalyst for hydrogen evolution reaction (HER) is reported, and its high HER activity is attributed to the synergetic effects of Ru doping and induced S vacancies in the MoS2, which reduce the energy barriers for H2 O dissociation and H* adsorption/desorption. This work provides an effective strategy to turn inert MoS2 into high‐activity electrocatalysts.